Implementation of Deconstruction Method Ideas In The Contemporary Theatre of Pilihan Pembayun Yogyakarta - Yudiaryani Yudiaryani; Hirwan Kuardhani; Silvia Anggreni Purba (Institut Seni Indonesia Yogyakarta, 2022)
The presence of contemporary theatre performing arts in Indonesia can not be separated from the history of theatrical performing arts in areas in Indonesia. “Contemporary” refers to the situation in space and time today and is a way of pointing to the development and change of theatre in these areas. Today’s performing arts are undergoing significant changes in their form and content. It was inspired by the discovery of science and technology and the dynamics of the world’s cultural ideas in the 20th century. Hans Thies Lehmann’s post-dramatic ideas around the 1980s in Europe, among others, inspired the emergence of new creativity studies internationally. Performing arts transformed itself from an ‘art performance’ into an intercultural and interdisciplinary performance of art by dismantling and rebuilding elements of its performances. The research theme is the development of science within art, while the research topic is the utilization of art theory to create works of art. The study aims to examine theories and deconstruction methods based on post-dramatic ideas that improve the quality of intercultural and gender theatre creation. The specific research target is to discover the benefits of deconstruction theory for creating contemporary theatre. The theatrical performance chosen in this study was The Pilihan Pembayun, a drama script by Hirwan Kuardhani and directed by Yudiaryani and Wahid Nurcahyono. Research methods use qualitative description methods. Qualitative methods look for the meaning behind data with interpretive and thorough analysis techniques. Data collection techniques with participant elevation, interviews, observations, field records, and documents will be used in the research. The research results obtained are the theoretical foundation for eliminating the negative aspects of intercultural and gender communication in the performing arts. Kehadiran seni pertunjukan teater kontemporer di Indonesia tidak lepas dari sejarah kehadiran seni pertunjukan di daerah-daerah di Indonesia.